Decompression Sickness during Construction of the Dartford Tunnel. Issue 3 (July 1960) - Golding, F. Campbell; Griffiths, P.; Hempleman, H. V.; Paton, W. D. M.; Walder, D. N.
Abstract : A clinical, radiological and statistical survey has been made of decompression sickness during the construction of the Dartford Tunnel. Over a period of two years, 1, 200 men were employed on eight-hour shifts at pressures up to 28 pounds per square inch (p.s.i.). There were 689 cases of decompression sickness out of 122, 000 compressions, an incidence of 0·56%. The majority of cases (94·9%) were simple "bends". The remainder (5·1%) exhibited signs and symptoms other than pain and were more serious. All cases were successfully treated and no fatality or permanent disability occurred. In two serious cases, cysts in the lungs were discovered. It is suggested that these gave rise to air embolism when the subjects were decompressed, and pulmonary changes may contribute more than hitherto believed to the pathogenesis of bends. Some other clinical features are described, including "skin-mottling" and an association between bends and the site of an injury. The bends rate is higher for the back shift (3 p.m. to 11 p.m.) and the night shift (11 p.m. to 7 a.m.) than for the day shift. In the treatment of decompression sickness it appears to be more satisfactory to use the minimum pressure required for relief of symptoms followed by slow decompression with occasional "soaks", than to attempt to drive the causative bubbles into solution with high pressures. During the contract the decompression tables recently prescribed by the Ministry of Labour were used. Evidence was obtained that they could be made safer, and that the two main assumptions on which they are based (that sickness will not occur at pressures below 18 p.s.i., and that a man saturates in four hours) may be incorrect. It is desirable to test tables based on 15 p.s.i. and eight-hour saturation. The existence of acclimatization to pressure was confirmed; it is such that the bends rate may fall in two to three weeks to 0·1% of the incidence on the first day of exposure. Acclimatization is lost again, with a "half-time" of about seven days, if a man is away from work. A study of bone damage in compressed air work has been started. In certain radiographs, abnormalities have been seen which may represent an early stage of caisson disease of bone.